(3GdNjGQGJ GdGSJQGJjLjI dfeh GdeDSSI (B:s (3GdCSS GdfXQjI dYedjI GdeaGVdI Hjf GdHOGFd GdGSJQGJjLjI ddfeh (B/s - (3Hf SGSj, EdjGSs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2011)
(3eGgjI feh GdeDSSGJ (B: (3eaghe feh GdeDSSGJ (B: (3eDTQGJ hMGdGJ Gdfeh (B: (3CgOGa haQU Gdfeh(B-(3GSJQGJjLjGJ feh GdeDSSGJ (B: (3GSJQGJjLjI Gdfeh Hjf GdgjefI hGdJejjR (B: (3GSJQGJjLjI Gdfeh Hjf GdJNUU hGdJfhjY(B-(3GdeDSSI Hjf NjGQj Gdfeh GdOGNdj hGdfeh GdNGQLj (B: (3NjGQGJ Gdfeh hETcGdjI GdeaGaje (B: (3GdeDSS CeGe NjGQ Gdfeh GdJYGbOj(B-(3eVehf YedjGJ Gdfeh GdOGNdj hGdfeh GdNGQLj (B: (3bQGQGJ GdGSJKeGQ hGdfeh GdOGNdj (B: (3CTcGd GdMjGRI aj Gdfeh GdNGQLj (B: (3COhGJ Jbjje GdGSJKeGQ hGNJjGQ HOjd Gdfeh GdefGSH(B-(3GdYhGed GdGbJUGOjI GdeJMceI aj YedjI GdeaGVdI Hjf Gdfeh GdOGNdj hGdfeh GdNGQLj (B: (3GdhUhd Edi GdMLe GdMQL (B: (3GdHMK Yf CKQ GdJCRQ(B-(3GdYhGed GdeGdjI GdeJMceI aj YedjI GdeaGVdI Hjf Gdfeh GdOGNdj hGdfeh GdNGQLj (B: (3eUGOQ Jehjd Gdfeh (B: (3GdeaGVdI Hjf NjGQj Gdfeh Hjf ChdhjGJ GdSjGSI GdeGdjI(B-(3GdYhGed GdbWGYjI GdeJMceI aj YedjI GdeaGVdI Hjf Gdfeh GdOGNdj hGdfeh GdNGQLj (B: (3OQLI fVL GdbWGY (B: (3MhGLR GdONhs
(3HHdjhZQGajG(B: (3U(B.299-308s
Keywords: (3EOGQI GdEfJGLs; (3GdEOGQI GdGSJQGJjLjIs; (3GdJfejI GdEbJUGOjIs; (3Gdfehs